Wojewoda w systemie organów bezpieczeństwa i porządku publicznego - Pieprzny, Stanisław (Studia Prawa Publicznego, 2023)
The aim of the article is to present the position of the voivode in the system of security authorities and public order in the voivodeship and its powers in relation to managers’ services, inspections and guards constituting the combined administration in the voivodeship. These powers developed since the introduction of the system reform in 1990 in relation to the creation of a dualism of local administrative bodies: local government at the commune level and local general government administration bodies. The basic rights of the voivode in the scope of safety and public order are currently defined in the Act of 23 January 2009 on the voivode and government administration in the voivodship. The Law the Police of 6th of April 1990 states that it is a body of security and public order at the voivodeship level, and that the voivodeship police chief represents the voivode in performing tasks in that regard, except for matters related to operational and exploratory investigations and prosecution of offences, as well as issuing individual administrative acts, if the laws so provide. The performance of tasks by the voivodeship police chief on behalf of the voivode does not mean, however, that the voivode is an official superior over the chief of police. Nor does grouping and superintendence imply the organisational inclusion of the auxiliary apparatus of the voivodeship chief of police in the provincial office, since it is the sovereign decision of the Chief Police Officer to determine the principles of organisation and the scope of action of chiefs. There is also no financial integration. The article also points out that the Act on the Voivode and Government Administration in the Voivodship defines the basic functions of the voivode, which include those related to public security and order in the voivodship. Particular tasks arising from these functions are defined by special laws, endowing the voivode with appropriate legal means for implementing these tasks, including authoritative means.